Daylighting and window design. (Lighting guide ;, 1999)
In designing windows for the provision of daylight it is important to avoid causing problems with glare, noise intrusion, summertime overheating and excessive use of energy. LG10: Daylighting and window design gives the designer a means of identifying the important factors and methods for solving some of the problems which inevitably occur. --